Structure of the Dicer-2–R2D2 heterodimer bound to a small RNA duplex - Yamaguchi, Sonomi; Naganuma, Masahiro; Nishizawa, Tomohiro; Kusakizako, Tsukasa; Tomari, Yukihide; Nishimasu, Hiroshi; Nureki, Osamu (Nature (London), 2022)
In flies, Argonaute2 (Ago2) and small interfering RNA (siRNA) form an RNA-induced silencing complex to repress viral transcripts 1 . The RNase III enzyme Dicer-2 associates with its partner protein R2D2 and cleaves long double-stranded RNAs to produce 21-nucleotide siRNA duplexes, which are then loaded into Ago2 in a defined orientation 2 – 5 . Here we report cryo-electron microscopy structures of the Dicer-2–R2D2 and Dicer-2–R2D2–siRNA complexes. R2D2 interacts with the helicase domain and the central linker of Dicer-2 to inhibit the promiscuous processing of microRNA precursors by Dicer-2. Notably, our structure represents the strand-selection state in the siRNA-loading process, and reveals that R2D2 asymmetrically recognizes the end of the siRNA duplex with the higher base-pairing stability, and the other end is exposed to the solvent and is accessible by Ago2. Our findings explain how R2D2 senses the thermodynamic asymmetry of the siRNA and facilitates the siRNA loading into Ago2 in a defined orientation, thereby determining which strand of the siRNA duplex is used by Ago2 as the guide strand for target silencing. Cryo-electron microscopy structures of Drosophila Dicer-2–R2D2 complexes with and without small interfering RNA reveal how the RNA is presented to Argonaute in the correct orientation for viral gene silencing.